Peran Teori Budaya Organisasi dalam Meningkatkan Motivasi Dan Kinerja Karyawan di PT Ferron Par Pharmaceuticals - Umi Fajriyah; Azzah Nabilah; Nandini Putri; Risya Aulia Rihadatul’aisy; Rismawati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This research investigates how organizational culture theory influences employee motivation and performance at PT Ferron Par Pharmaceuticals. All the values, norms, and practices embraced by each member of the organization are referred to as 'organizational culture,' and this can affect performance and work behavior. Organizational culture theory helps us understand how elements like leadership, communication, core values, and employee engagement can create a supportive work environment. This study shows that a strong organizational culture aligned with company values can enhance employee motivation, increase their sense of belonging to the company, and help them achieve their work targets more effectively. At PT Ferron Par Pharmaceuticals, a cooperative, creative, and quality-oriented work culture has proven to improve productivity and employee satisfaction. Thus, understanding and effectively managing organizational culture becomes a strategic factor in the development of human resources and the achievement of company goals. Therefore, a good understanding and management of organizational culture is an important strategic component to enhance human resources and achieve company objectives.